2019
DOI: 10.1371/journal.pone.0216504
|View full text |Cite
|
Sign up to set email alerts
|

Elephant (Elephas maximus) temporal activity, distribution, and habitat use patterns on the tiger’s forgotten trails across the seasonally dry, subtropical, hilly Churia forests of Nepal

Abstract: Understanding spatial distribution, habitat use, and temporal activity patterns is important for species conservation planning. This information especially is crucial for mega herbivores like elephants as their ranging patterns encompass a myriad of habitats types. Churia habitat is geological fragile yet important for wildlife in Nepal and India. We used camera trapping and sign surveys covering 536 km 2 of Churia and surrounding areas within Chitwan National Park. Across 152 trapping l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Elephant attacks inside forests peaked during the afternoon (~16:00) when human activity, mainly cattle grazing, and fodder and forest resource collection would remain high inside the forests. The elephants generally rest during the mid‐day hot period and start become active with decreasing temperature in the afternoon (after 15:00) (Thapa et al., 2019 ). This increases the chance of interaction between elephants and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Elephant attacks inside forests peaked during the afternoon (~16:00) when human activity, mainly cattle grazing, and fodder and forest resource collection would remain high inside the forests. The elephants generally rest during the mid‐day hot period and start become active with decreasing temperature in the afternoon (after 15:00) (Thapa et al., 2019 ). This increases the chance of interaction between elephants and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 34 ] shows coefficient of determination, expressed as R 2 , found to be significant between NDVI and Bamboo vegetation indices at 65% and 52% with or without presence of canopy in the wet season. We used Landsat 6 Thematic Mapper imagery to derive NDVI covariate [ 23 ] and images were extracted for monsoon season that matched with the timing of the 2016 survey period. GIS data characterizing the NDVI metrics (range: -0.50–0.82) were clipped and averaged for each grid cell.…”
Section: Methodsmentioning
confidence: 99%
“…Division of the major grid cells into six sub-grid cells was primarily designed for the logistical reason (geographic complexity and terrain condition) and improving detection history of secretive animal. We chose for spatial replication over temporal [19] primarily for logistical reasons as done in previous studies for large mammals [20][21][22][23]. Adequate sign detections, replications and spatial coverage can be achieved with adequate survey efforts per grid cells and careful planning [20].…”
Section: Field Designmentioning
confidence: 99%
“…Due to the large numbers of images collected, researchers may save time by focusing only on those that contain animals of interest, leaving many images as 'bycatch'. These images might contain very useful data on many other species [49,50], but are often left unanalysed.…”
Section: Camera Traps and Citizen Sciencementioning
confidence: 99%